2015
DOI: 10.6061/clinics/2015(01)04
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width is associated with myocardial injury in non-ST-elevation acute coronary syndrome

Abstract: OBJECTIVES:The red blood cell distribution width has been associated with an increased risk of cardiovascular events. In the present study, we assessed the relationship between red cell distribution width values and cardiac troponin I levels in patients admitted with non-ST-elevation acute coronary syndrome.METHODS:We analyzed blood parameters in 251 adult patients who were consecutively admitted to the intensive coronary care unit with non-ST-elevation acute coronary syndrome over a 1-year period. For all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Increased RDW in a patient with CAD, leads to increased risk of Heart failure as shown by Felker et al in 2007. 2 RDW was found to be useful in triaging patients with NSTEACS as NSTEMI in a cohort of 251 patients admitted to coronary care unit over one year period by Erhan Tenekecioglu et al 13 Baseline RDW correlated well with MGS and was having increased positive predictive value of atherosclerotic burden. The RDW has been reported to be a predictor of coronary heart disease events and all cause mortality in various cardiovascular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Increased RDW in a patient with CAD, leads to increased risk of Heart failure as shown by Felker et al in 2007. 2 RDW was found to be useful in triaging patients with NSTEACS as NSTEMI in a cohort of 251 patients admitted to coronary care unit over one year period by Erhan Tenekecioglu et al 13 Baseline RDW correlated well with MGS and was having increased positive predictive value of atherosclerotic burden. The RDW has been reported to be a predictor of coronary heart disease events and all cause mortality in various cardiovascular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Danese et al showed that elevated RDW in a patient with CAD leads to an elevated risk of heart failure (35). RDW was detected to be helpful in triaging patients with non-ST-elevation ACS in a cohort of 251 patients referred to coronary care unit over one year period by Tenekecioglu et al (36).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Lippi et al[28] suggested that high RDW should be used together with cardiac markers in patients admitted to the ED. Tenekecioglu et al[29] found that RDW was higher in patients diagnosed with NSTEMI than patients diagnosed with UA. They showed that RDW showed a positive correlation with cTn I.…”
Section: Discussionmentioning
confidence: 99%